1998
DOI: 10.1063/1.368109
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of ball milled copper ferrite

Abstract: The structural and magnetic evolution in copper ferrite (CuFe 2 O 4 ͒ caused by high-energy ball milling are investigated by x-ray diffraction, Mössbauer spectroscopy, and magnetization measurements. Initially, the milling process reduces the average grain size of CuFe 2 O 4 to about 6 nm and induces cation redistribution between A and B sites. These nanometer-sized particles show superparamagnetic relaxation effects at room temperature. It is found that the magnetization is not saturated even with an applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
99
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(110 citation statements)
references
References 26 publications
(18 reference statements)
11
99
0
Order By: Relevance
“…Many authors mentioned this problem in their works on mechanochemistr y. Moreover, some concrete examples of the possible participation of the milling tools' material in mechanochemical processes were reported [13][14][15][16][17][18][19][20][21] , but these works have not been followed up on.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors mentioned this problem in their works on mechanochemistr y. Moreover, some concrete examples of the possible participation of the milling tools' material in mechanochemical processes were reported [13][14][15][16][17][18][19][20][21] , but these works have not been followed up on.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Goya et al 20) , who followed the phase evolution of CuFe2O4 during high-energy ball milling in a steel vial, it was shown that a two-phase mixture consisting of magnetite and a spinel solid solution (CuxFe3-XO4) yields the final product of the mechanical treatment of Cu-ferrite. This indicates that the high-energy milling of the oxide generates a complex series of solid-state transformations, including mechanochemical decomposition and reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) it can be seen that all loops are closed which indicates low anisotropy field and low saturation magnetization field . The copper ferrite is known to be magnetically soft, with value of coercively of about 0.7 kOe at room temperature for bulk material [17] . For hexagonal Cu ferrite, these values are different as shown in Fig.…”
Section: Magnetic Studymentioning
confidence: 99%
“…In the case of milling, one of the aims is to reduce the crystallite sizes and reach the nanometric size scale. For example, the bulk ferrite materials Fe 3 O 4 [7,8], ZnFe 2 O 4 [9], and CuFe 2 O 4 [10] were milled and the nanometric sizes were obtained. Milling is more effective when the bulk material is milled in a liquid such as acetone, methanol, or others.…”
Section: Introductionmentioning
confidence: 99%